PENGAWASAN STANDAR UJI KELAYAKAN KENDARAAN BERMOTOR DI KOTA PEKANBARU (STUDI KASUS : ANGKUTAN KOTA) - Refkisyam, Zaiwandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Pekanbaru city as the capital of Riau province experiencing rapid population growth. Increasing the number of residents will have an impact on the use of means of transportation in order to fulfill their needs. In everyday life people need a means of transportation that is safe and convenient to traverse various regions. Pekanbaru city government did one of them presses the number of private vehicles and increase public transportation. One of the public transport in the city of Pekanbaru namely transportation (public transportation). But in fact that happened is still a lot of public transportation (public transportation) were not roadworthy because it does not meet the technical standards and standards of road-worthy vehicle. Urban transportation conditions like this would not be able to provide comfort and safety to the user community. The research objective is to identify and analyze the feasibility test standard surveillance of motor vehicles (Case Study: City Transport) and to determine the factors that hinder the standard regulatory process feasibility test motor vehicles (Case Study: City Transport).The concept of the theory used is the starting Supervision the process of setting standards, measuring or assessing and taking corrective action. This study uses qualitative research methods to study descriptive data. In collecting the data, the authors use the technique of interview, observation, and documentation. By using key informants as a source of information and data analysis.The results of this study indicate that the regulatory process feasibility studies for urban transport is carried out by the Motor Vehicle Testing UPTD Dishubkominfo not run entirely in accordance with standard operating procedures. The process of due diligence supervision of urban transportation is not running because it is still irregularities in the testing process. This has an impact on urban transport conditions are not roadworthy still operating in the city of Pekanbaru. Meanwhile factors - factors inhibiting the regulatory process is the amount of human resources is still lacking. Availability of funds / test equipment repair costs that can not be immediately in use. So the need for evaluation of the policies of use of budget funds and increasing the number of motor vehicle testing officers in the city of Pekanbaru.Keywords: Curbing, traffic and Road Transport